Usability and Accessibility in Assistive Technology for Visually Impaired (Human Factors in Design, 2025)
This study presents a systematic review focused on identification and analysis of the use of usability and accessibility guidelines in Assistive Technologies (AT) for visually impaired. The research analyzes nine papers and the perspectives of four renowned authors in the field of usability and the development of interactive systems. The study also highlights five insights found in the papers, considered fundamental in the development of AT. The conclusion points to the importance of using these guidelines, as currently, the limited integration of specialized knowledge in this area leads to a restriction in the effective development of applications.
Keywords: Assistive Technology; Visual Impairment; Usability; Accessibility; Guidelines